A Soft Pressure Sensor Array Based on a Conducting Nanomembrane - Daekwang Jung; Kyumin Kang; Hyunjin Jung; Duhwan Seong; Soojung An; Jiyong Yoon; Wooseok Kim; Mikyung Shin; Hyoung Won Baac; Sangmin Won; Changhwan Shin; Donghee Son (Micromachines, 2021)
Although skin-like pressure sensors exhibit high sensitivity with a high performance over a wide area, they have limitations owing to the critical issue of being linear only in a narrow strain range. Various strategies have been proposed to improve the performance of soft pressure sensors, but such a nonlinearity issue still exists and the sensors are only effective within a very narrow strain range. Herein, we fabricated a highly sensitive multi-channel pressure sensor array by using a simple thermal evaporation process of conducting nanomembranes onto a stretchable substrate. A rigid-island structure capable of dissipating accumulated strain energy induced by external mechanical stimuli was adopted for the sensor. The performance of the sensor was precisely controlled by optimizing the thickness of the stretchable substrate and the number of serpentines of an Au membrane. The fabricated sensor exhibited a sensitivity of 0.675 kPa−1 in the broad pressure range of 2.3–50 kPa with linearity (~0.990), and good stability (>300 Cycles). Finally, we successfully demonstrated a mapping of pressure distribution.